Fear of Black Europe: Race in Medieval and Early Modern Video Games - Anderson, Austin (KULA, 2025)
Video games set in or inspired by early modern or medieval Europe have historically featured almost entirely white casts of characters, a decision often defended on the grounds of historical accuracy. This video essay examines how the myth of an all-white European past emerged and how it has shaped both video game design and gaming culture more broadly. It then explores how diversity is represented in the For Honor and Chivalry series as case studies of the "historical accuracy" framing in video games. Ultimately, the essay argues that including a diverse cast of characters is not only appropriate but necessary for achieving true historical accuracy.